Chemotherapeutic response to cisplatin-like drugs in human breast cancer cells probed by vibrational microspectroscopy - Carvalho, A. L. M. Batista de (2016)
Studies of drug-cell interactions in cancer model systems are essential in the preclinical stage of rational drug design, which relies on a thorough understanding of the mechanisms underlying cytotoxic activity and biological effects, at a molecular level. This study aimed at applying complementary vibrational spectroscopy methods to evaluate the cellular impact of two Pt(ii) and Pd(ii) dinuclear chelates with spermine (Pt2Spm and Pd2Spm), using cisplatin (cis-Pt(NH3)2Cl2) as a reference compound. Their effects on cellular metabolism were monitored in a human triple-negative metastatic breast cancer cell line (MDA-MB-231) by Raman and synchrotron-radiation infrared microspectroscopies, for different drug concentrations (2-8 μM) at 48 h exposure. Multivariate data analysis was applied (unsupervised PCA), unveiling drug- and concentration-dependent effects: apart from discrimination between control and drug-treated cells, a clear separation was obtained for the different agents studied - mononuclear vs. polynuclear, and Pt(ii) vs. Pd(ii). Spectral biomarkers of drug action were identified, as well as the cellular response to the chemotherapeutic insult. The main effect of the tested compounds was found to be on DNA, lipids and proteins, the Pd(ii) agent having a more significant impact on proteins while its Pt(ii) homologue affected the cellular lipid content at lower concentrations, which suggests the occurrence of distinct and unconventional pathways of cytotoxicity for these dinuclear polyamine complexes. Raman and FTIR microspectroscopies were confirmed as powerful non-invasive techniques to obtain unique spectral signatures of the biochemical impact and physiological reaction of cells to anticancer agents.